Comparison between microwave ablation and lobectomy for stage I non-small cell lung cancer: a propensity score analysis. (17th November 2018) - Yao, Wang; Lu, Mingjian; Fan, Wenzhe; Huang, Jinhua; Gu, Yangkui; Gao, Fei; Wang, Yu; Li, Jiaping; Zhu, Zhihua
Abstract: Purpose: To compare the effectiveness and complication between microwave ablation and lobectomy for stage I non-small cell lung cancer. Materials and Methods: This retrospective study was approved by two institutional ethics committees and all patients were provided with informed consent. From January 2000 to December 2010, 54 and 795 stage I patients who underwent microwave ablation and lobectomy were included in this study. A matched cohort composed of 54 and 108 patients in the microwave ablation and the lobectomy group were selected after adjustment with 1:2 propensity score matching. The overall survival and disease-free survival were evaluated. Survival curves were constructed with the Kaplan–Meier method and compared by using the log-rank test. Results: The 1, 3 and 5-year Overall survive were 100, 92.6 and 50.0% for MWA group and 100, 90.7 and 46.3% for lobectomy group. The 1, 3 and 5-year disease free survival was 98.1, 79.6 and 37.0% for MWA group and 98.1, 81.5 and 29.6% for lobectomy group. There was no significant difference between two groups in overall survival ( p = 0.608) and disease free survival ( p = 0.672). Additionally, local or distant metastasis rate ( p = 0.544) were not significantly different between two groups while the complication rate in the MWA group was significantly lower than the lobectomy group ( p = 0.008). Conclusion: Microwave ablation has similar therapeutic effect compared with lobectomy for stage I non-small cell lung cancer, but with fewer complication and less pain.